Case Report: Integrated traditional Chinese and Western medicine in the outpatient management of diabetic foot gangrene complicating uremia - Hu, Can; Chen, Jian (Frontiers in Endocrinology, 2025)
Diabetic foot gangrene (DFG) in uremic patients presents profound management challenges due to immune dysfunction and impaired tissue repair. We report on a 65-year-old male patient with end-stage renal disease undergoing peritoneal dialysis, presenting with progressive right foot gangrene that was unresponsive to conventional treatment. Clinical evaluation indicated extensive gangrene affecting the first and second toes, elevated inflammatory markers (C-reactive protein at 95.57 mg/L and fibrinogen at 8.18 g/L), and cardiovascular compromise (brain natriuretic peptide at 4869 pg/mL). Lower limb computed tomography angiography confirmed severe atherosclerosis. An integrated protocol combining Yanghe Sijunzi Decoction with meticulous debridement and localized analgesia was implemented over 7 months (18 outpatient visits). This approach resulted in complete ulcer healing by October 2024, with the resolution of gangrene, an 87% reduction in CRP levels (to 12 mg/L), normalization of coagulation markers, and preservation of foot function—thus preventing amputation. Patient-reported outcomes, including pain scores and sleep duration gradually improved as healing advanced from 23 March 2024. The total treatment costs amounted to 25,000 CNY, with the patient’s share being 5,000 CNY, demonstrating cost-efficiency. This case highlights Traditional Chinese Medicine’s potential as an immunomodulatory adjuvant in uremia-associated DFG, modulating inflammation and promoting tissue regeneration in high-risk patients.